The Efficiency of Upstream Petroleum Contracts: Risk Service Contract in Focus - Taherifard, Ali; Farimani, Fazel Moridi; Negin-Taji, Zarir (International Journal of Energy Economics and Policy, 2025)
Upstream contracts in petroleum sector may alter the behaviour of the contractor. This alteration may deviate the production path from the optimal one; this adverse effect is called distortionary effect of contracts. In this paper the distortionary effect of a risk service contract is evaluated using the data from an oil field in Middle East. The field is operated under a risk service contract signed in 2000 to increase the production by around 80,000 bbl/day. The contractual production profile (proposed by the contractor and stipulated within the contract) is compared against the estimated optimal production path over the contract life-cycle (2000-2024) and with the actual production. The optimal production path is calculated in both finite and infinite case using stochastic dynamic programming method. Results reveal that under different scenarios of discount rate, depletion rate and gas injection, the contractual production falls below the optimal production path which results in a loss of cumulative production of 5- 34% over the contract lifecycle. It is also shown that actual production is also below the optimal path and the path suggested by the contractor within the contract. It is discussed how contract time limitation affects adversely on the cumulative production of the field. Inflexibilities in contractual elements such as cap on total recoverable costs, stringent work program and upper/lower limit of production profile are discussed to be the main sources of distortion.